PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN DARI BARANG BEKAS TERHADAP PENINGKATAN KEMAMPUAN GURU MADARASAH AL-RAISIYAH SEKARBELA, KOTA MATARAM - agustiningsih, neneng (LPPM UBT, 2017)
Objective of the dedication is to give provisioning toward teachers, accustom to use media in learning process to increase motivation, interest, and students activeness, improving teachers creativity in increasing learning process of IPA at Madarasah Al-Raisiyah, Sekarbela. Methods of the dedication are workshop and training. The strategies are 1. Observation and interview, 2. mapping of capability and problem 3. Training preparation 4. Workshop with Yusuf M.Pd. and Nurmiti, M.Pd. as informant and training by team of SGI, evaluation using quetionnaire. Based on the training, the teachers made several kinds of medium as are pop up, repiration model and static movement, display and advertisement. Through associating for three times, IPA teacher made pop up medium for animal clasification, animal reproduction and tissue of plants. Result of the questionnaire shows total score is 645 with its average is 43 with description : the participants need training, media are very important in learning process, used goods are needed as solution in making media.